2019
DOI: 10.1371/journal.pone.0219664
|View full text |Cite|
|
Sign up to set email alerts
|

Human indole(ethyl)amine-N-methyltransferase (hINMT) catalyzed methylation of tryptamine, dimethylsulfide and dimethylselenide is enhanced under reducing conditions - A comparison between 254C and 254F, two common hINMT variants

Abstract: Phenylalanine and cysteine comprise common miss-sense variants (i.e., single nucleotide polymorphisms [SNPs]) at amino acid position 254 of the human indole(ethyl)amine-N-methyltransferase (hINMT). The phenylalanine variant, which occurs in linkage disequilibrium with two 3’ UTR SNPs, has been reported to associate with elevated urine levels of trimethylselenonium (TMSe), the Se-methylated product of volatile dimethylselenide. hINMT allozymes expressing either cysteine (254C) or phenylalanine (254F) at positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…18,19 Previous works suggested that mouse and human INMT proteins drove the methylation of dimethylsulfide, dimethylselenide, and dimethyltelluride as substrates. 20,21 However, it is still unclear how INMT commits to produce TMSe for urinary Se excretion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Previous works suggested that mouse and human INMT proteins drove the methylation of dimethylsulfide, dimethylselenide, and dimethyltelluride as substrates. 20,21 However, it is still unclear how INMT commits to produce TMSe for urinary Se excretion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indolethylamine N -methyltransferase (INMT) is another methyltransferase that catalyzes double methylation of tryptamine to produce N , N -dimethyltryptamine . The TMSe concentration in blood and urine correlated with single nucleotide polymorphisms in the INMT gene by a genome wide association study between the TMSe-producing and nonproducing individuals. , Previous works suggested that mouse and human INMT proteins drove the methylation of dimethylsulfide, dimethylselenide, and dimethyltelluride as substrates. , However, it is still unclear how INMT commits to produce TMSe for urinary Se excretion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the research and development of biomarkers associated with prostate cancer metastasis, including prostate-specific antigen (PSA), androgen receptor splice variant 7 (ARV7), and transforming growth factor-beta (TGFβ), might guide the early treatment decision of tumor metastasis and significantly improve outcomes (Kretschmer and Tilki, 2017;Manca et al, 2017;Bastos and Antonarakis, 2018). Indolethylamine-N-methyltransferase (INMT) is a methyltransferase that regulates the N-methylation of tryptamine family proteins (Chu et al, 2014;Torres et al, 2019). It is associated with the development and activity of the nervous system and participates in the detoxification of selenium compounds (Kim et al, 2015;Kuehnelt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indolethylamine-N-methyltransferase (INMT) is a methyltransferase that regulates the N-methylation of tryptamine family proteins ( Chu et al, 2014 ; Torres et al, 2019 ). It is associated with the development and activity of the nervous system and participates in the detoxification of selenium compounds ( Kim et al, 2015 ; Kuehnelt et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indolethylamine N-methyltransferase (INMT) is a methyltransferase that regulates the tryptophan metabolic pathway by catalyzing the N-methylation of tryptamine and structurally related compounds ( Chu et al, 2014 ; Torres et al, 2019 ). As a thioether S-methyltransferase, it also plays an important role in the detoxification of selenium compounds ( Kuehnelt et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%